Rancang Bangun Teknologi Peningkatan Konversi Energi Menggunakan Pembersih Debu Otomatis Dan Reflektor Pada Panel Surya Berbasis Mikrokontroler Arduino - Michael Owen Sihotang; Habib Satria (Universitas Medan Area, 2025)
Solar energy is one of the most potential renewable energy sources, but the performance of solar panels can decrease due to dust accumulation on the panel surface. This study aims to design and build an automatic dust cleaning tool based on an Arduino microcontroller equipped with a reflector to increase energy conversion in solar panels. This system uses a dust sensor to detect the level of dirt on the panel, as well as a drive motor to automatically clean the panel surface when the dust reaches a certain level. Based on the test results, there was an increase in the output voltage of the solar panel after the cleaning process, with an average increase of 0.5 to 1.5 Volts. In addition, the use of a reflector helps increase the intensity of light received by the panel, especially in the morning and evening. With this automatic system, the efficiency of the solar panel can be maintained without periodic manual intervention. The results of the study indicate that this tool is effective in improving the performance of solar panels and has the potential to be applied to small to medium-scale installations.